Born of deception - Brown, Teri J. (2014)
Moving to London in the 1920s to join a prestigious European vaudeville tour and reunite with her boyfriend Cole, budding illusionist Anna must harness her special powers and navigate the underworld of magic before her murderous enemies catch up with her.
Sequel to: Born of illusion.
Keywords: Psychic ability -- Fiction; Magicians -- Fiction; Secret societies -- Fiction; Love -- Fiction; Psychic ability -- Fiction; Magicians -- Fiction; Secret societies -- Fiction; Europe -- History -- 1918-1945 -- Fiction; Europe -- History -- 1918-1945 -- Fiction